QUALITY MANAGEMENT FOR DEVELOPMENT OF MEDICAL DEVICE SOFTWARE - Juolahti, Johannes (My University, 2020)
This master’s thesis’ purpose is to study the role of a quality management system in agile software development in the field of medical device software (MDS). More specifically, this thesis will focus on the intersection of general software development quality assurance and different regulations concerning medical devices and the effect that they pose on the requirements for the quality assurance (QA) for a business operating in this field.